Revolutionizing Agriculture Through Space Science and Technology Applications - Njoku, Placid Chike (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
KEYNOTE ADDRESS AT THE CENTRE FOR SATELLITE TECHNOLOGY DEVELOPMENT ANNUAL WEEK, 2018 HELD AT THE CENTRE IN ABUJA ON 14 -15 AUGUST, 2018